2023
DOI: 10.1136/jitc-2022-006649
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic suppression of type I interferon production underlies the therapeutic efficacy of IL-15-producing natural killer cells in B-cell acute lymphoblastic leukemia

Abstract: BackgroundType I interferons (IFN-Is), secreted by hematopoietic cells, drive immune surveillance of solid tumors. However, the mechanisms of suppression of IFN-I-driven immune responses in hematopoietic malignancies including B-cell acute lymphoblastic leukemia (B-ALL) are unknown.MethodsUsing high-dimensional cytometry, we delineate the defects in IFN-I production and IFN-I-driven immune responses in high-grade primary human and mouse B-ALLs. We develop natural killer (NK) cells as therapies to counter the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…We found that MYC+BCL2+ B cells can cause an inflammatory microenvironment with immunosuppressive characteristics through some immune inflammatory signaling pathways. This is consistent with the conclusion of recent studies, which showed that lymphoma cells with obvious proliferative characteristics have the potential to induce a ‘depleted’ microenvironment ( 32 34 ). The patient in this case was not only confirmed as a double-expressed patient by immunohistochemistry, but at the cellular level, we also identified a malignant B subgroup of “MYC+ BCL2+”, indicating high proliferation of B cells in the patient’s tumor.…”
Section: Discussionsupporting
confidence: 93%
“…We found that MYC+BCL2+ B cells can cause an inflammatory microenvironment with immunosuppressive characteristics through some immune inflammatory signaling pathways. This is consistent with the conclusion of recent studies, which showed that lymphoma cells with obvious proliferative characteristics have the potential to induce a ‘depleted’ microenvironment ( 32 34 ). The patient in this case was not only confirmed as a double-expressed patient by immunohistochemistry, but at the cellular level, we also identified a malignant B subgroup of “MYC+ BCL2+”, indicating high proliferation of B cells in the patient’s tumor.…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, they can have a crucial—even primary—role in disease. Other mutations at low prevalence and even low effect may also be crucially important in a distinct co-occurring genetic context [ 45 , 46 ] or molecularly defined subtype [ 5 , 47 ]; for instance, the single-nucleotide mutations of CDKN2A in B-cell and T-cell ALL have a low estimate of effect ignoring context, but the high frequency of CDKN2A deletions and their co-occurrence with substitutions (3 out of 5 T-ALL patients with CDKN2A substitutions have the focal deletion of the other copy; among B-ALL patients, 4 out of 12) indicate a large selective epistatic effect. Prioritizing the investigation of these high-impact targets not only opens new avenues for potentially highly effective therapeutic targets but also provides valuable insights into the intricate mechanisms driving the disease, thereby advancing our understanding and ultimately leading to improvements in precision therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“… 39 , 40 However, increased IFN-related gene expression in MSC after contact with leukemic cells may also reflect an anti-leukemic response of MSC in the tumor microenvironment to attract other immune cells. 31 , 41 , 42 A recent study by Kumar et al showed that reduced production of IFNα/β, leading to decreased NK-cell surveillance, promotes development of B-ALL in vivo. 42 Restoring this IFNα/β production allows for NK effector cells to reduce leukemia progression in mice that are prone to MYC-driven B-ALL.…”
Section: Discussionmentioning
confidence: 99%
“… 31 , 41 , 42 A recent study by Kumar et al showed that reduced production of IFNα/β, leading to decreased NK-cell surveillance, promotes development of B-ALL in vivo. 42 Restoring this IFNα/β production allows for NK effector cells to reduce leukemia progression in mice that are prone to MYC-driven B-ALL. In high-risk acute myeloid leukemia, IFNα/β administration after hematopoietic stem cell transplantation may be effective in preventing relapse.…”
Section: Discussionmentioning
confidence: 99%